An automated flight control system for quadrotor flying vehicle using embedded microcontroller - Yeo, Ivan. (2012)
Vertical Take-Off and Landing (VTOL) Unmanned Aerial Vehicle (UAV) aircrafts have been an active area of research in recent years. With the advent of low-cost Micro-Electro-Mechanical Systems (MEMs) sensors, it has become viable to construct models of VTOL aircrafts for controller design and comparison. Leveraging the strengths of the Renesas H8S/2378 16-bit Microcontroller, a Quadrotor system has been designed and implemented.This report focuses on: